SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN KREDIT PADA PT. ADIRA QUANTUM DUMAI DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) MENGUNAKAN BAHASA PEMOGRAMAN VISUAL BASIC 6.0 - -, Masrizal (Jurnal Informatika, 2016)
PT. Adira Quantum Dumai branch is a business entity serving the community in the field of credit services that aim to meet the needs and desires of the community quickly which helps the consumer to have high-quality goods through fixed installment facility and affordable. But the company Adira Quantum branch Dumai this time not all runs smoothly and professionally because there are some problems in the process of data management, including in decision-making is often the incompatibility of the customer who gets the credit in accordance with the value of the criteria and the weights are determined by the company, the length of the submission of reports decision to the head of the company and customer information to make the decision-making process than the prospective customer credit beneficiary. Decision Support System (DSS) is designed to solve the problems in determining the feasibility of providing credit to customers at PT. Adira Quantum Branch DumaiÂ Key Words : credit, DSS, SAW Methods